Análisis osteológico de ejemplares delfín de Fraser (Lagenodelphis hosei Fraser, 1956) provenientes de la costa de la provincia de Buenos Aires, Argentina - Lucero, Sergio Omar (2009)
The presence of Lagenodelphis hosei in temperate waters of the Argentinian Sea is a rare event because of its preference for pelagic and tropical waters. With the aim to increment the available information on the Fraser´s dolphin in Soutwestern Atlantic waters, we made a morphological and morphometric analysis of skull and postcranial skeleton of five specimens stranded at the end of the 2000 year, in the La Plata River, between Punta Lara and Magdalena localities, at Buenos Aires Province, Argentina. The results were compared with data source from non-South American areas. We observed that specimens of the Southwestern Atlantic described in this study tend to have larger braincase size and the size relation of external nares between males and females is inverse to that seen in specimens of geographically distant areas.